Argon plasma coagulation with atezolizumab and chemoradiation in lung pleomorphic cancer showed a remarkable response: Case report. Issue 21 (28th May 2021) - Harada, Masanori; Morikawa, Keisuke; Kagoo, Namio; Ito, Yutaro; Kubota, Tsutomu; Ichijo, Koshiro; Mochizuki, Eisuke; Uehara, Masahiro; Matsuura, Shun; Yasuda, Kazuyo; Tsukui, Masaru; Koshimizu, Naoki
Abstract: Rationale: Lung pleomorphic carcinoma (LPC) is generally resistant to chemotherapy or radiotherapy. However, a combination of immune checkpoint inhibitors and radiotherapy has a remarkable efficacy against LPC. Patient Concerns and Diagnoses: Here, we report the case of a 50-year old man diagnosed with progressive LPC. The tumor invaded the carina and predominantly obstructed the right main bronchus; therefore, a combination of palliative chemoradiotherapy and atezolizumab was initiated. However the trachea was gradually obstructed. Intervention and Outcome: Argon plasma coagulation (APC) was performed to prevent tumor invasion. After three APC sessions, the tumor showed a necrotic change and was easily excised using biopsy forceps. Lessons: A combination of chemoradiotherapy, atezolizumab, and APC showed a good efficacy, and the patient had a good response to atezolizumab maintenance therapy. Multidisciplinary treatments, such as a combination of immune checkpoint inhibitors and APC, could have synergistic efficacy in lung cancer.